Under the aegis of Aphrodite: on the feminine space in The Awakening, by Kate Chopin - Rossi, Aparecido Donizete (Revista de Letras, 2010)
Departing from the theoretical principle of the feminine text as a palimpsest that holds subtextual meanings which, in permanent interaction with the textual surface, disarticulate the oppositional and hierarchical backgrounds of patriarchy, this essay intends to off er a general overview on the narrative instance of space in The Awakening, the most important work by Kate Chopin . one of the highlights of Realism in the United States ., with the intention to show how the space is itself plenty of and at the same time disseminates into the other narrative elements some inter-dictions to gainsay patriarchy. We intend, in this perspective, to develop an analysis of the space and its subtextual inter-relationships displayed in the symbolic implications of the water, the sea, the circle, and the feminine subjectivity awakening of the work fs protagonist.Keywords: The Awakening. Kate Chopin. Space. Palimpsest. Subtext.